Evaluation of the Effectiveness of Cost Leadership Strategies in Reducing Operating Costs of Manufacturing Companies - Christina Situmorang, Vera (Riviera Publishing, 2024)
Evaluation of the effectiveness of a cost leadership strategy should also consider external factors that can affect the operating costs of a manufacturing company. The purpose of this study is to determine the effect of the implementation of cost leadership strategies on the reduction of raw material costs in manufacturing companies and to determine the impact of cost leadership strategies on production efficiency and product quality in manufacturing companies as well as to determine the perception of managers and employees on the effectiveness of cost leadership strategies in achieving cost savings goals in manufacturing companies. The method used in this study is qualitative descriptive. The results in this study are Internal factors that influence the success of this strategy include a corporate culture that supports innovation and efficiency, management involvement at all levels, appropriate incentive systems, and good integration with supply chain management. In addition, adaptability to external changes such as fluctuations in commodity prices is also key in maintaining the success of this strategy. In order to achieve the long-term goal of increasing profitability and sustainability, companies need to consider all of these factors holistically.